2020
DOI: 10.1002/yea.3445
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genetics revisited

Abstract: Mitochondrial genetics started decades ago with the discovery of yeast mutants that ignored the Mendelian rules of inheritance. Today, the many known DNA sequences of this second eukaryotic genome illustrate its eccentricity in terms of informational content and functional organisation, suggesting a yet incomplete understanding of its evolution. The hereditary transmission of mitochondrial alleles relies on complex mixes of molecular and cellular mechanisms in which recombination and limited sampling, two sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 144 publications
2
53
0
Order By: Relevance
“…This is likely driven by isolates with very close mitochondrial sequence often also having similar nuclear genome sequence, while the main branches of the mitochondrial tree cannot be positioned with confidence. Overall, our results highlight a pronounced separation in evolutionary histories of the two co-existing genomes and the extensive recombination found provides additional support to yeast mitochondrial inheritance requiring recombination-driven replication (Kowalczykowski 2000;Chen and Clark-Walker 2018;Dujon 2019).…”
Section: Extensive Admixture Of Mitochondrial Genomessupporting
confidence: 59%
See 1 more Smart Citation
“…This is likely driven by isolates with very close mitochondrial sequence often also having similar nuclear genome sequence, while the main branches of the mitochondrial tree cannot be positioned with confidence. Overall, our results highlight a pronounced separation in evolutionary histories of the two co-existing genomes and the extensive recombination found provides additional support to yeast mitochondrial inheritance requiring recombination-driven replication (Kowalczykowski 2000;Chen and Clark-Walker 2018;Dujon 2019).…”
Section: Extensive Admixture Of Mitochondrial Genomessupporting
confidence: 59%
“…The S. cerevisiae yeast has long been considered as an organism with an almost clonal reproduction and strictly uniparental mitochondrial inheritance (Dujon 2019). Nevertheless, the scenario emerging from our phylogenetic analyses revealed that outbreeding and recombination drive mitochondrial genome evolution.…”
Section: Discussionmentioning
confidence: 96%
“…Meiotic daughter cells inherit mtDNA from both parents [ 16 , 17 ], but the proportions of each parental mtDNA depends on the position from which the daughter cell emerges from the zygote: buds that originate from the middle of the zygote are heteroplasmic and contain both parental mtDNA, and buds that originate from either end of the zygote are nearly homoplasmic [ 18 ]. These heteroplasmic daughter cells can obtain homoplasmy within 20 mitotic divisions [ 19 ].…”
Section: Discovery Of Umi In Fungi and Cryptococcusmentioning
confidence: 99%
“…xation of a single mitochondrial haplotype (mitotype) [43,44]. Controlled laboratory experiments allowing for mitochondrial recombination revealed that reassorting naturally-occurring alleles from different mitochondrial loci could produce functional differences [45,46] and provide the opportunity to investigate tness effects of coadapted mitonuclear alleles at high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled laboratory experiments allowing for mitochondrial recombination revealed that reassorting naturally-occurring alleles from different mitochondrial loci could produce functional differences [45,46] and provide the opportunity to investigate tness effects of coadapted mitonuclear alleles at high resolution. Advanced molecular tools for exploring mitochondrial mechanisms [43,47] and an expanded knowledge of population genetics in Saccharomyces [48] further promote yeast as an exciting mitonuclear model.…”
Section: Introductionmentioning
confidence: 99%